Digital accessibility: Challenges and opportunities. Issue 1 (March 2019) - Kulkarni, Mukta
Abstract: This round table is focussed on outlining barriers to digital accessibility, solutions, and possible next steps to ensuring digital accessibility. In setting the context of the round table discussion, the article first outlines what accessibility involves, accessibility standards and guidelines, and spells out barriers to accessibility, including the limitations posed by the institutional context and the technology context. It also discusses the status of digital accessibility in India. The article then reports on a panel discussion in which diverse stakeholders discussed several of the issues outlined above.